(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Il contributo, sottoposto a valutazione, è stato pensato nell’ambito del progetto di ricerca (finanziato dall’Istituto di Studi Politici “S. Pio V” di Roma), in corso di pubblicazione, dal titolo Cittadinanza e religione nel Mediterraneo e nell’epoca della globalizzazione e delle diversità. SOMMARIO: 1. Premessa – 2. Dallo stato di natura al contratto sociale – 3. Conclusioni: dallo stato di natura (“inter-statale”) alla “trasfigurazione” del Leviatano. ABSTRACT: This article aims at analyzing the relationship between citizenship and religion, taking its inspiration from the Thomas Hobbes’ thought. The Author try to propose a dialogue-based approach between the two different conceptual categories, also considering the fibrillations of today’s geo-political scenarios, starting from the Mediterranean area. In this perspective, he thinks that we need a necessary "transfiguration" of the Leviathan in order to promote – through a fertile dialogue between aims and values – a deeper revision of both the concept of sovereignty and the role of a constitutional State. Which is even more relevant with the reference to the issues of today’s multicultural society.